KRAS-related miR-143 expression is associated with lymph node involvement and correlates with outcome in pancreatic adenocarcinoma patients - Lavacchi, Daniele; Polvani, Simone; Taddei, Antonio; Scolari, Federico; Messerini, Luca; Caliman, Enrico; Moraldi, Luca; Guidolin, Alessia; Grazi, Gian Luca; Galli, Andrea; Pillozzi, Serena; Antonuzzo, Lorenzo (Frontiers in Oncology, 2023)
Introduction Pancreatic adenocarcinoma (PC) is one of the most lethal malignancies; even after resection the patients’ 5-year disease-free survival (DFS) is lower than 26%. The genetic mutational landscape of PC is dominated by activating KRAS mutations, that have been reported in approximately 90% of cases; however, beyond KRAS - direct mutations, several KRAS-targeting miRNAs appear to be downregulated, strengthening the already activated RAS signaling. In addition, the interplay between miRNAs and RAS includes poorly investigated downstream miRNAs. The aim of this study was to determine the prognostic value of some of these candidate KRAS-related miRNAs. Patients and methods Between 2015 and 2022, 44 patients with pathologically confirmed PC, who received surgery and were enrolled by the Clinical Oncology Unit, Careggi University Hospital, Florence (Italy). PC Total RNA was extracted from FFPE sections, retro-transcribed and the resulting cDNA was then used for qPCR analysis. A panel of KRAS-related miRNA (miR-155, miR-206 and miR-143) was analyzed. Results In this observational study patients sex distribution was unequal with 34.1% being male and 65.9% female. The most frequent tumor localization was the head of the pancreas (65.9%) and the pathological stages were pT1-2 (45.5%), pT3 (54.5%), pN0 (22.7%), pN+ (77.3%). Adjuvant therapy was administered to 63.6% of patients; disease recurrence was observed in 69% of cases. Twenty-three patients, whose RNA was of adequate quality, were used in the mRNAs expression studies. When comparing the miRNA expression between PC and a pool of healthy tissues, miR-155 was overexpressed and miR-206 downregulated in PC, while miR-143 expression was unchanged. However, when categorized in low- and high- miR-143 expressing PC (according to the median value), high miR-143 was associated with nodal involvement (pN+) (p=0.029), who in turn was linked with shorter DFS (p=0.009) and overall survival (OS) (p=0.021) compared to pN0. A trend toward inferior DFS was observed for higher expression of miR-206 (p=0.095) and miR-143 (p=0.092). Finally, responders to a first-line treatment for advanced disease had miR-155 overexpressed (p=0.048). Conclusions miRNAs are involved in PC tumorigenesis and metastatic spread. In light of miR-143 association with lymphatic spread and poor prognosis, a comprehensive analysis of miRNA interplay with KRAS deserves further investigation.